Utilization of Caulerpa sp. as a feed ingredient for growth and survival of whiteleg shrimp and Chanos chanos in polyculture - Nasmia; Syahir Natsir; Rusaini; Akbar Marzuki Tahya; Jusri Nilawati; Siti Nurdjana Ismail (Egyptian Journal of Aquatic Research, 2022)
The addition of seaweed Caulerpa sp. flour to the whiteleg shrimp and Chanos chanos feed is a viable alternative to lower the feed costs by reducing the usage of imported materials. The current study is planned to transform the seaweed into a feed material that is rich in nutrients and bioactive compounds that can boost whiteleg shrimp and C. chanos growth and survival. A completely randomized design is applied in the present study with four levels of Caulerpa sp. flour addition, each with 3 replications. The experimental animals used were juveniles of the whiteleg shrimp at a stocking density of 20 ind. tank−1 and C. chanos of 0.89–1.18 g. ind-1 at a stocking density of 10 ind. tank−1, polycultured in 30-L aquaria for 30 days. The statistical analysis showed that the addition of Caulerpa sp. flour at different doses had significantly affected the specific growth rate of the C. chanos and the absolute growth of the whiteleg shrimp (P < 0.05). The highest feed efficiency was achieved with the addition of 6% Caulerpa sp. flour (55.16% ± 0.09), whereas the lowest value was recorded in the treatment of no Caulerpa sp. flour addition (38.59% ± 2.02). The highest feed conversion ratio was obtained when no Caulerpa sp. flour was added (1.57) and the lowest value was recorded in the treatment of 6% Caulerpa sp. flour addition (1.20 ± 0.06).